Fluoroless 3D mapping‐guided pacemaker implant in a pregnant patient. Issue 9 (14th June 2021) - Gianni, Carola; Della Rocca, Domenico G.; Natale, Andrea; Horton, Rodney P.
Abstract: We describe a case of pacemaker implant guided by intracardiac echocardiography and three‐dimensional anatomical mapping in a pregnant patient, with no peri‐procedural use of radiation.